ANALYSIS OF BPJS KETENAGAKERJAAN AGENCY SYSTEM WITH LEGAL CERTAINTY - Dewa Ayu Asti Puspitawati; Budi Santoso (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The inconsistency of informal sector participant acquisition activities by Perisai agents is also an impact of weak supervision of BPJS Ketenagakerjaan as the principal. The purpose of this study is to determine and analyze the implementation of the basic principles of agency in the BPJS Ketenagakerjaan agency system and to determine and analyze the BPJS Ketenagakerjaan agency system model that has legal certainty. The type of research used in this study is juridical-normative. The specifications in this study are analytical descriptive research. The data collected were then analyzed using qualitative analysis methods. BPJS Ketenagakerjaan Board of Directors Regulation Number: 13/PERDIR.02/042022 Concerning the BPJS Ketenagakerjaan Agency System defines the Indonesian Social Security Driving Agent as an individual who is a member of the Wadah and has met the requirements set by BPJS Ketenagakerjaan. The definition of the Indonesian Social Security Driving Agent does not describe the legal relationship as the definition of an agent is a party who receives the authority given by the principal to carry out certain legal acts for and on behalf of its principal. This is crucial considering that in practice agency problems often occur, such as issues of authority, principal responsibility and responsibility towards third parties.